2020
DOI: 10.3390/ijms21197095
|View full text |Cite
|
Sign up to set email alerts
|

MOS1 Negatively Regulates Sugar Responses and Anthocyanin Biosynthesis in Arabidopsis

Abstract: Sugars, which are important signaling molecules, regulate diverse biological processes in plants. However, the convergent regulatory mechanisms governing these physiological activities have not been fully elucidated. MODIFIER OF snc1-1 (MOS1), a modulator of plant immunity, also regulates floral transition, cell cycle control, and other biological processes. However, there was no evidence of whether this protein was involved in sugar responses. In this study, we found that the loss-of-function mutant mos1-6 (m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…HXK1 plays versatile roles in plant growth, development, and sugar sensing (Huang et al, 2019; Zheng et al, 2019; Li et al, 2020b; Barbier et al, 2021). HXK1 has been reported to positively regulate plant immunity to pathogens by controlling ROS and anthocyanin accumulation and stomatal closure (Hu et al, 2016; Li et al, 2018; Ye et al, 2020; Zhang et al, 2020; Wang et al, 2021c). Similarly, we found that overexpressing OsHXK1 enhanced resistance to M. oryzae infection by inducing ROS accumulation (Figure 2B–D).…”
Section: Discussionmentioning
confidence: 99%
“…HXK1 plays versatile roles in plant growth, development, and sugar sensing (Huang et al, 2019; Zheng et al, 2019; Li et al, 2020b; Barbier et al, 2021). HXK1 has been reported to positively regulate plant immunity to pathogens by controlling ROS and anthocyanin accumulation and stomatal closure (Hu et al, 2016; Li et al, 2018; Ye et al, 2020; Zhang et al, 2020; Wang et al, 2021c). Similarly, we found that overexpressing OsHXK1 enhanced resistance to M. oryzae infection by inducing ROS accumulation (Figure 2B–D).…”
Section: Discussionmentioning
confidence: 99%
“…MOS1 performs various regulatory activities in multiple aspects of plant growth, including the flowering time, cell cycle, and stress responses in Arabidopsis [ 27 , 28 , 31 , 32 ]. Here, we focused on the functional characterization of a rice MOS1 , OsMOS1 , which is a close homolog of Arabidopsis MOS1 as it contains the conserved BAT2 domain.…”
Section: Discussionmentioning
confidence: 99%
“…The defection of endopolyploidization in the mos1 mutant can be suppressed by the mutations of SUF4 , but not FLC , indicating that MOS1 modulates the endopolyploidization and flowering time through different genetic pathways [ 27 ]. In addition, MOS1 negatively regulates sugar responses and anthocyanin biosynthesis in Arabidopsis , possibly at the transcriptional level [ 32 ]. Thus, the existing finding indicates that MOS1 functions as a key coordinator in the regulation of growth and biotic and abiotic stress responses in Arabidopsis .…”
Section: Introductionmentioning
confidence: 99%